Hospitality and manifestations among the Arabs before Islam - Hussein, Mohammed A. (Humanities Journal of University of Zakho, 2015)
Generally, The hospitality is considered the most important social values ​​and appearances in several nations and that importance is varied from people to another and from one environment to another. Some tribes regarded hospitality as the most important qualities that to be proud of and Arab poets had always praised such quality, and composed verses to glorify their tribes, particularly the gentlemen who are notorious for their good hospitalities and their commitment to literature and traditions. This study has shed the light on this phenomenon among the Arabs in the era before Islam, providing a definition of hospitality in the language and terminology, and study of the hospitality among Arabs before Islam in terms of its appearance and its inception as well as revenue several of the views of a group of researchers and historians with discussions. Furthermore, the study deals with all manifestations of the Arabs before Islam in which was the most important that the hospitality constituted a manifestation of sovereignty continued to be on some of the habits of the Arabs in the hospitality and what they were doing in order to bring guests to their homes, such as lighting the fire and linking them to the dogs outside rackets tribe for the purpose of bringing the attention of the guests to the house. In addition, the study tackles the study of hospitality by some religious manifestations that were prevalent in the study period as delegations which was carried out by the people of Mecca and was represented by an important factor linking through Mecca and its inhabitants to the rest of the population of the Arabian Peninsula who make pilgrimages to it each year. Moreover, the study mentions some people who coupled names generosity and hospitality of the Arabs such as Hashim bin Abdul Manaf al-Qurashi, Hatem al-Tai and Abdullah bin Jad'aan Taymi